Examining the role of maturity status on physical performance: A case study in the Spanish volleyball talent development programme - de la Rubia, A.; Molina-Martín, J. J.; Muriarte-Solana, D.; Veiga, S.; Nieto-Acevedo, R.; López-Serrano, C. (International Journal of Sports Science & Coaching, 2025)
Maturation is one of the determining factors in talent identification and development systems. The aim of the present study was to assess the impact of maturity status and anthropometric variables on the physical performance of young volleyball players. The sample included 278 volleyball players (217 girls, 13.63 ± 1.73 years; and 61 boys, 14.27 ± 1.46 years) who were selected to participate in the 2020-2025 National Programme organised by the Spanish Volleyball Federation. Maturity status was estimated using the Khamis-Roche equation based on the percentage of predicted adult height. The physical tests evaluated were vertical jump, spike jump reach, 3 × 9 and FRAC. The results showed that an advanced maturation is associated with increased physical performance in young volleyball players. Specifically, `maturity status` was strongly and positively associated with the VJ (p < 0.001), SJR (p < 0.001) and 3 × 9 (p < 0.001) tests in both boys and girls, and `height` was associated with the VJ (girls, p < 0.001; boys, p < 0.01), SJR (p < 0.001, both) and 3 × 9 (girls, p < 0.001; boys, p < 0.01). `Body mass` correlated with vertical jump tests (VJ and SJR), especially in girls (p < 0.001). Moreover, the maturity status in relation to age served as a predictor of physical performance in the SJR test explaining up to 57.93% and 62.00% of the variance in boys and girls respectively. Coaches and technical staffs should rethink the tests used in talent identification in order to avoid confusing the player's current potential with the future sporting level through actions such as adapting the training process or implementing educational initiatives in relation to maturation.